2001
DOI: 10.1076/clin.15.2.196.1892
|View full text |Cite
|
Sign up to set email alerts
|

Effective Screening for Alzheimers Disease Among Older African Americans

Abstract: Relatively little data exist concerning the utility of brief cognitive measures to detect dementia among African Americans. The current study evaluated the clinical utility of the Mini-Mental Status Exam (MMSE) and the Fuld Object Memory Evaluation (FOME) in detecting Alzheimer's disease (AD) among both African American and European American older adults. One hundred and forty geriatric patients from a large urban academic medical center were examined. Overall, the FOME appeared to be more effective in detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 15 publications
4
23
0
1
Order By: Relevance
“…Consistent with previous studies (La Rue, 1989;Marcopulos et al, 1999;Mast et al, 2001;Wall et al, 1998), participants' performance on FOME was not influenced by the level of education, regardless of the level of cognitive functioning. The sample of this study had a fairly similar distribution across the three levels of education, albeit there were a higher proportion of participants in the dementia group who did not have any education.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previous studies (La Rue, 1989;Marcopulos et al, 1999;Mast et al, 2001;Wall et al, 1998), participants' performance on FOME was not influenced by the level of education, regardless of the level of cognitive functioning. The sample of this study had a fairly similar distribution across the three levels of education, albeit there were a higher proportion of participants in the dementia group who did not have any education.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, they are similar to those obtained in overseas studies. Mast et al (2001) proposed a cutoff score of 30 for TR in a community elderly sample that comprised of American Africans and European Africans. Marcopulos et al (1999) reported that a cutoff score of 8 for DR demonstrated good ability to differentiate geriatric patients with dementia from community normal controls and patients with psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literatürde kognitif yaşlanmanın 20-30 lu yaşlarda başladığı gösterilmiş olsa da, çoğu çalışma 60 yaş üstüne odaklanmıştır 10 22 . Bizim çalışmamızda benzer şekilde MMSE ile eğitim arasında pozitif korelasyon gözlenmekle birlikte, MMSE ile yaş arasında negatif korelasyon gözlenmiştir.…”
Section: Discussionunclassified